Internalisasi Nilai-Nilai Maqashid Syariah Dalam Psikoterapi Keluarga Muslim - Ma’isyatuts Tsalitsah, Imtihanatul (Muhammadiyah University of Surabaya, 2024)
This study aims to explore the internalization of the values of Maqashid Syariah in Muslim family psychotherapy, focusing on how Islamic principles can be integrated into family therapy to improve quality of life. Maqashid Syariah refers to the fundamental objectives or principles in Islam that serve as guidelines for various aspects of life, including psychotherapy. Muslim family psychotherapy, grounded in Islamic principles, is expected to have a positive impact on enhancing the mental, emotional, and social well-being of family members. This study uses a qualitative approach with a case study of Muslim families who have participated in family therapy sessions based on the values of Maqashid Syariah. The results indicate that values such as the preservation of religion (hifz ad-din), life (hifz an-nafs), intellect (hifz al-‘aql), lineage (hifz an-nasl), and wealth (hifz al-mal) can be internalized in family psychotherapy practice, leading to significant positive impacts on family relationships and helping them face life’s challenges in a more wise and balanced manner. Thus, applying the principles of Maqashid Syariah in family therapy not only improves the quality of relationships among family members but also strengthens their spiritual and mental closeness, ultimately contributing to overall family harmony. Keywords: Maqashid Syariah, Family Psychotherapy, Muslim Family Well-being,Islamic Values.